Recombinant Human Bone Morphogenic Protein-2 Immobilized Fabrication of Magnesium Functionalized Injectable Hydrogels for Controlled-Delivery and Osteogenic Differentiation of Rat Bone Marrow-Derived Mesenchymal Stem Cells in Femoral Head Necrosis Repair - Lu, Xueliang; Guo, Hongyu; Li, Jiaju; Sun, Tianyu; Xiong, Mingyue (Frontiers in Cell and Developmental Biology, 2021)
Femoral head necrosis (FHN) is a clinically progressive disease that leads to overwhelming complications without an effective therapeutic approach. In recent decades, transplantation of mesenchymal stem cells (MSCs) has played a promising role in the treatment of FHN in the initial stage; however, the success rate is still low due to unsuitable cell carriers and abridged osteogenic differentiation of the transplanted MSCs. Biopolymeric-derived hydrogels have been extensively applied as effective cell carriers and drug vesicles; they provide the most promising contributions in the fields of tissue engineering and regenerative medicine. However, the clinical potential of hydrogels may be limited due to inappropriate gelation, swelling, mechanical characteristics, toxicity in the cross-linking process, and self-healing ability. Naturally, gelated commercial hydrogels are not suitable for cell injection and infiltration because of their static network structure. In this study, we designed a novel thermo-gelling injectable hydrogel using natural silk fibroin-blended chitosan incorporated with magnesium (Mg) substitutes to improve physical cross-linking, stability, and cell osteogenic compatibility. The presented observations demonstrate that the developed injectable hydrogels can facilitate the controlled delivery of immobilized rhBMP-2 and rBMSCs with greater cell encapsulation efficiency, compatibility, and osteogenic differentiation. In addition, outcomes of in vivo animal studies established promising osteoinductive, bone mineral density, and bone formation rate after implantation of the injectable hydrogel scaffolds. Therefore, the developed hydrogels have great potential for clinical applications of femoral head necrosis therapy.